A new species of the Scinax catharinae Group (Anura: Hylidae) from Northeastern Brazil - Calijorne Lourenco, Ana Carolina [UNESP]; Celeste Luna, Maria; Pombal Júnior, José P. (Magnolia Press, 2014)
We describe a new species of the Scinax catharinae Group from Municipality of Porto Seguro, State of Bahia northeastern Brazil. The new species is mainly characterized by its small size, nuptial pad dark colored, and compound pectoral fold. Additionally, we describe the structure of its nuptial pad and compare it with that of S. agilis. We also briefly discuss its phylogenetic relationships within Scinax.
Keywords: Dendropsophini; Nuptial pad; Morphology; Systematics